Clinicopathologic correlations of genomic gains and losses in follicular lymphoma - Viardot, Andreas; Möller, Peter; Högel, Josef; Werner, Kirsten; Mechtersheimer, Gunhild; Ho, Anthony Dick; Ott, German; Barth, Thomas F. E.; Siebert, Reiner; Gesk, Stefan; Schlegelberger, Brigitte; Döhner, Hartmut; et al. (Journal of clinical oncology, 2002)
PURPOSE: To evaluate the clinical relevance of genomic aberrations in follicular lymphomas (FLs). - - PATIENTS AND METHODS: In this study, we analyzed 124 biopsy samples of patients with FL using comparative genomic hybridization. - - RESULTS: In 87 cases (70%), genomic imbalances were detectable. The most frequent aberrations were gains of chromosome arms 7p (21 patients), 7q (21 patients), Xp (16 patients), 12q (15 patients), and 18q (14 patients) as well as losses on 6q (21 patients). Grades 2 and 3 according to the World Health Organization classification correlated with a more complex karyotype (P < .0001). In a subset of 82 patients, a comprehensive clinical data set was available. In a multivariate analysis including all clinical risk factors of the International Prognostic Index as well as genomic aberrations, the loss of material on chromosomal bands 6q25q27 was the strongest predictor of a shorter survival (P = .0001; hazard ratio, 6.5), followed by elevated serum lactate dehydrogenase level (P = .0009; hazard ratio, 4.9), the presence of more than one extranodal manifestation (P = .017; hazard ratio, 4.2), and age greater than 60 years (P = .022; hazard ratio, 2.6). - - CONCLUSION: These data indicate that genomic aberrations may contribute significantly to risk assessment in patients with FL, the majority of whom are included in low-risk groups using established clinical prognostic scores.
Gesehen am 10.12.2021